Contenido de cadmio en almendras de Theobroma cacao I. (CACAO) considerando variedades, condiciones agroecológicas y manejo industrial en las provincias de Los Ríos y Cotopaxi año 2018 - Baraja Palomo, Edgar (2019)
The purpose of this work is to determine the levels of cadmium (Cd) in the soil, almonds and leads of the CCN51 and National cocoa crop, in the provinces of Ríos and Cotopaxi. In Ecuador, contents of this element have been reported in cocoa almonds, exceeding the maximum levels allowed by international regulations on processed products, which generates monitoring alerts in order to guarantee product safety. Plants absorb cadmium from available forms of this element in the soil leading to the fruit. The investigation was carried out in the two provinces, which consisted of collecting samples from different points of the two provinces of the soil and almonds and foliar to determine the transfer of cadmium (Cd) in soil and almonds and foliar analyzed in the laboratory, according to the permissible levels established by the European Union is 0.20mg / kg, the cadmium content of the different sites evaluated, as for the soil, a higher content of cadmium was presented in the Quevedo canton (0.35 mg / kg) In the foliar part of cocoa there was a higher content of cadmium in the Pangua canton (3.12 mg / kg). In the powder obtained from the cocoa bean, there was a higher content of cadmium in the Pangua canton (1.34 mg / kg), it was observed that in the subtropical part of Cotopaxi it is above the permissible limits established by the regulations current environmental. Keywords: cadmium, maximum levels, cocoa, absorption, soil and almonds